Curbing Unemployment and Brain Drain Among Nigerian Youths Through Islamic Financing Instruments - Ibraheem Alani AbdulKareem; Kamoru Mutiu Olaide; Onimajesin Salihu Isiaka (Journal of Islamic Economic and Business Research, 2021)
The alarming increase in graduates/youths unemployment across the globe is disturbing. Graduates/youths unemployment that leads to brain drain is a complex problem facing developing countries, of which Nigeria is not spared. It is on this premise that necessitated the purpose of writing this paper is to ameliorate the issue of graduate/youth unemployment through the adoption of Islamic financing instruments as a solution to curb this high rate of graduates/youths unemployment in Nigeria. Going by the focus of this paper, Islamic financing instruments which have been seen to be under-utilized but if aggressively encouraged by the Nigerian government through easy access to funding by graduates/youths, which is a catalyst to entrepreneurship among graduates/youths to reduce unemployment that has been combating them and the nation at large. The method employed for this study is conceptual in nature. It reviewed previous literature whereby understanding the roles played by Islamic financing in curbing the menace of brain drain and unemployment among graduates/youth were gained. Based on the understanding of reviewed literature, this study has documented that Islamic finance instrument has played a significant role in SMEs. The study also found out that the impact of harnessing SMEs through Islamic finance instruments cannot be ignored in any society. Thus, it is suggested that the Nigerian government should embrace Islamic financing to reduce the population of graduates/youths who have recently, as a matter of no job, partake in ENDSARS protests and roaming the streets aimlessly across Nigeria. The implication of study on the Nigeria government and policymaker in term of adoption of Islamic finance instruments was to address the issues of SMEs in order to tame the menace on unemployment and brain drain, thereby retaining our graduate/youths to contribute their quotas through their skills/potentials for the betterment of the country.